The Progresses, Pageants, and Entertainments of Queen Elizabeth I. - Archer, Jayne Elisabeth (OUP Oxford, 2007)
The reign of Elizabeth I was a Golden Age of English culture. Part of Elizabeth's policy of 'popular monarchy' took the form of tours throughout southern England and the Midlands. In return, her hosts staged theatrical performances, pageants, and entertainments. These essays explore the Elizabethan progresses from a range of perspectives. - ;More than any other English monarch before or since, Queen Elizabeth I used her annual progresses to shape her royal persona and to bolster her popularity and authority. During the spring and summer, accompanied by her court, Elizabeth toured southern Engl.